2010
DOI: 10.1136/jcp.2010.087478
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heparan sulfate in gastric carcinoma and its correlation with clinicopathological features and patient survival

Abstract: The data suggest that heparan sulfate may play an important role in regulating the biology of gastric cancer, and that it may be a useful prognostic marker of this tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…In addition, we found that PTK7 expression was associated with differentiation and survival in gastric cancer patients. Similar reports demonstrated that some prognostic markers were associated with differentiation 18, 19. Several important differentiation‐related factors also have been linked with gastric cancer survival 20, 21.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, we found that PTK7 expression was associated with differentiation and survival in gastric cancer patients. Similar reports demonstrated that some prognostic markers were associated with differentiation 18, 19. Several important differentiation‐related factors also have been linked with gastric cancer survival 20, 21.…”
Section: Discussionsupporting
confidence: 68%
“…The human PTK7 gene is located in a region (6p21.1–p12.2) of the chromosome where deletions and duplications are frequently found among patients with developmental disorders and several cancers 18, 22. It has been proven that PTK7 inhibits tube formation as well as the migration and invasion of endothelial cells and angiogenesis 23.…”
Section: Discussionmentioning
confidence: 99%
“…41 Genetic incorporation of poly-lysines and Arg-Gly-Asp (RGD) peptides into the fiber knob makes it possible for a recombinant Ad to infect vi a heparan sulfate and α v -integrins, respectively 42–44 ; however, downregulation of heparin sulfate was reported in several types of tumors. 45 , 46 Although fiber-modified conditionally replicating Ads containing RGD peptides in the fiber knob infect CTCs via interaction with α v -integrins, CD46 is an infection receptor suitable for infection of CTCs with conditionally replicating Ads because CD46 was upregulated in malignant tumor cells. 19 , 20 In addition, CD46 was not downregulated under TGF-β–induced EMT ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of CS showed prognostic capacity in breast [128] and ovarian cancers [130]. High expression levels of HS signaled poor prognosis in patients with gastric carcinoma [131]. Higher levels of HA were associated with poor survival in patients with breast cancer [133], acute myeloid leukemia [134], and prostate cancer [132].…”
Section: Gags and Gps In Diagnosis And Prognosismentioning
confidence: 99%